2005
DOI: 10.1128/iai.73.2.1006-1013.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential PsaA-, PspA-, PspC-, and PdB-Specific Immune Responses in a Mouse Model of Pneumococcal Carriage

Abstract: Larger numbers of pneumococci were detected in the nasal tract compared to the lung, cervical lymph nodes, and spleen 1, 2, 4, 7, 14, and 21 days after nasal challenge with Streptococcus pneumoniae strain EF3030. In this mouse model of pneumococcal carriage, peripheral S. pneumoniae pneumococcal surface adhesin A (PsaA)-specific humoral responses (immunoglobulin G2a [IgG2a] Ͼ Ͼ IgG1 ‫؍‬ IgG2b > IgG3) were significantly higher than pneumococcal surface protein A (PspA)-specific, genetic toxoid derivative of pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 58 publications
(47 reference statements)
5
35
0
2
Order By: Relevance
“…This procedure produced a mean carriage of 5 ϫ 10 6 pneumococci per nasopharyngeal tissue after 48 h, without any evidence of disease. These numbers are in agreement with other studies using the EF3030 strain (13,55,62). Pneumococcal growth in the tissues was verified by morphology of the bacteria on blood agar plates in combination with testing several isolated clones for optochin sensitivity.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This procedure produced a mean carriage of 5 ϫ 10 6 pneumococci per nasopharyngeal tissue after 48 h, without any evidence of disease. These numbers are in agreement with other studies using the EF3030 strain (13,55,62). Pneumococcal growth in the tissues was verified by morphology of the bacteria on blood agar plates in combination with testing several isolated clones for optochin sensitivity.…”
Section: Resultssupporting
confidence: 79%
“…Although a role of biofilm formation during pneumococcal disease has been shown, the growth phenotype of bacteria colonizing the human nasopharynx, its main biological niche, has not been visually documented. To obtain the best chance of observing biofilm formation in vivo and to produce the most clinically relevant colonization possible, we inoculated BALB/cByJ mice intranasally for 48 h with a clinical strain of pneumococci, EF3030, that has been well documented, by us and others, to effectively establish noninvasive colonization of high bacterial density (4,55,62). This procedure produced a mean carriage of 5 ϫ 10 6 pneumococci per nasopharyngeal tissue after 48 h, without any evidence of disease.…”
Section: Resultsmentioning
confidence: 99%
“…Mutation in the psaA gene caused pleiotropic effects on the growth, oxidative stress response, adherence, and virulence of S. pneumoniae (14). PsaA was also found to be one of the main pneumococcal antigens and causes a distinct immune response in a mouse model which is different from those mediated by other pneumococcal antigens (25). Another group of well-known bacterial adhesins are pili or fimbriae (28).…”
Section: Discussionmentioning
confidence: 99%
“…Briles et al (10) demonstrated that sera from PspA-immunized individ-uals protect mice from fatal infection with S. pneumoniae expressing PspAs of different families. Studies of the local and systemic immune responses against PspA have raised evidence that antibodies to PspA could prevent NP colonization in humans and mice (20,25). Thus, on the basis of its immunogenic properties, PspA could be an alternative antigen in a vaccine formulation aimed at attaining a strong impact on the prevention of pneumococcal NP colonization, in addition to protecting against invasive disease.…”
mentioning
confidence: 99%